2021
DOI: 10.1093/bib/bbab146
|View full text |Cite
|
Sign up to set email alerts
|

nhKcr: a new bioinformatics tool for predicting crotonylation sites on human nonhistone proteins based on deep learning

Abstract: Lysine crotonylation (Kcr) is a newly discovered type of protein post-translational modification and has been reported to be involved in various pathophysiological processes. High-resolution mass spectrometry is the primary approach for identification of Kcr sites. However, experimental approaches for identifying Kcr sites are often time-consuming and expensive when compared with computational approaches. To date, several predictors for Kcr site prediction have been developed, most of which are capable of pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…In addition to those discussed, deep learning can also be applied for other PTMs’ predictions, including methylation [110] , S-nitrosylation [111] , succinylation [112] , [113] , malonylation [114] , [115] , S-sulphenylation [116] , [117] , crotonylation [118] , [119] , [120] , [121] , 2- hydroxyisobutyrylation [122] , glutarylation [123] , N-palmitoylation [124] carbonylation [125] , and SUMOylation [126] . In particular, crotonylation prediction has demonstrated highly accurate results based on deep-learning methods.…”
Section: Other Ptmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to those discussed, deep learning can also be applied for other PTMs’ predictions, including methylation [110] , S-nitrosylation [111] , succinylation [112] , [113] , malonylation [114] , [115] , S-sulphenylation [116] , [117] , crotonylation [118] , [119] , [120] , [121] , 2- hydroxyisobutyrylation [122] , glutarylation [123] , N-palmitoylation [124] carbonylation [125] , and SUMOylation [126] . In particular, crotonylation prediction has demonstrated highly accurate results based on deep-learning methods.…”
Section: Other Ptmsmentioning
confidence: 99%
“… 2020 [119] Deep-Kcr Crotonylation Human CNN 10-fold CV 19,928 https://lin-group.cn/server/Deep-Kcr 2020 [120] DeepKcrot Crotonylation Multiple CNN WE 10-fold CV and independent test 10,702/1,265/2,044/5,995 * https://www.bioinfogo.org/deepkcrot . 2021 [121] nhKcr Crotonylation Human CNNrgb 10-fold CV and independent test 180,312 https://nhKcr.erc.monash.edu/ 2021 [118] DeepKhib 2-Hydroxyisobutyrylation Multiple CNN OH 10-fold CV and independent test 18,946/15,444/12,756/19,330/2,098 * https://www.bioinfogo.org/DeepKhib . 2020 [122] DeepGlut Glutarylation Prokaryotes and Eukaryote CNN 10-fold CV 4,572 * https://github.com/urmisen/DeepGlut .…”
Section: Other Ptmsmentioning
confidence: 99%
“…In 2018, 5,995 sites on 2,120 proteins had first been extracted and released by Liu, K. et al Liu et al (2018) and provided more experimental-verified crotonylated samples in plant Carica papaya L, which filled in the gaps of lacking samples in computational analysis of crotonylation. Based on these Carica papaya L. data, Zhao, Y et al have carried out a prediction on the large dataset, in which the deep learning method has been involved Zhao et al (2020) and more deep learning-related methods were released, such as “DeepKcr” Lv et al (2021) and “nhKcr” Chen Y. Z. et al (2021) .…”
Section: Introductionmentioning
confidence: 99%
“…Later, five traditional ML-based models were developed, including support vector machine (SVM) model by Qiu et al [10] , CKSAAP_CrotSite (SVM) [11] , iKcr-PseEns (ensemble random forest, RF) [12] , LightGBM-CroSite (LightGBM) [13] , and random forest (RF)/SVM classifiers by Wang et al [14] . The remaining five were all built on the frame of deep learning (DL), including iCrotoK-PseAAC [15] , pKcr [16] , Deep-Kcr [17] , DeepKcrot [18] and nhKcr [19] . Throughout these predictors, we can observed that: in terms of datasets, the early tools mainly concentrated on histone or mixed data, whereas the recent works began to study nonhistone proteins due to the enrichment of high-throughout nonhistone data.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout these predictors, we can observed that: in terms of datasets, the early tools mainly concentrated on histone or mixed data, whereas the recent works began to study nonhistone proteins due to the enrichment of high-throughout nonhistone data. Accordingly, the number of samples sharply increased from 34/90 (the number of positive samples over negative samples) in the first model CrotPred [9] to 15,605/75,111 in the latest model nhKcr [19] , which can effectively guarantee the statistical significance of the constructed models; in terms of protein features, it roughly covered several classical easy-interpreted descriptors (i.e., composition of k-spaced amino acid pairs (CKSAAP), one-hot, enhanced amino acid composition (EAAC), pseudo-amino acid composition (PseAAC), pseudo-position specific scoring matrix (PsePSSM), etc) and deep learning representation embedding methods (i.e., wording embedding (WE)); in terms of algorithms, researchers were more inclined to choose deep learning techniques rather than conventional classifiers; as for model evaluation, recent works strictly completed cross validation and independent tests to get objective and reliable results.…”
Section: Introductionmentioning
confidence: 99%